2003
DOI: 10.1046/j.1524-4733.2003.64238.x
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Effectiveness Analysis of Eletriptan 40 and 80 mg versus Sumatriptan 50 and 100 mg in the Acute Treatment of Migraine

Abstract: Further refinement of outcomes measurement in migraine would be valuable and eletriptan has a potentially important role to play in the cost-effective management of the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…A total of fourteen CEA or CUA studies were identified. Of these, six were conducted in the United States, 15-21 four in the United Kingdom, [22][23][24][25] three in Canada, 21, 26,27 and one in Belgium 28 (Table 1). A substantial amount of literature since the 1990s has been devoted to the investigation of the economic burden of migraines in different countries during recent decades.…”
Section: Economic Analyses For Migrainementioning
confidence: 99%
See 1 more Smart Citation
“…A total of fourteen CEA or CUA studies were identified. Of these, six were conducted in the United States, 15-21 four in the United Kingdom, [22][23][24][25] three in Canada, 21, 26,27 and one in Belgium 28 (Table 1). A substantial amount of literature since the 1990s has been devoted to the investigation of the economic burden of migraines in different countries during recent decades.…”
Section: Economic Analyses For Migrainementioning
confidence: 99%
“…As illustrated in Table 1, several studies focusing on only a few types of triptans have had the advantage of using controlled clinical trial studies to obtain the efficacy and resource use data. 16,[22][23][24] However, those studies that compared all types of triptans available in the market have used the data from the metaanalysis 36 due to the lack of comparative clinical trial studies of all triptans. The meta-analysis study conducted by Ferrari et al 36 used raw patient data provided by the trial investigators or sponsors and so included only those clinical trials of triptan therapies with similar design and similar patient population.…”
Section: Source Of Datamentioning
confidence: 99%
“…Triptans in general have shown to be cost effective in reducing this burden [41]. In one study, the cost for migraine attack was lower for eletriptan compared with sumatriptan [42]. Eletriptan has been shown to be associated with a > 50% reduction in time loss compared with placebo [43].…”
Section: Pharmacoeconomical Aspectsmentioning
confidence: 99%
“…The difference is that between efficacy and real clinical effectiveness. For example, a study reported success in 64-67% for eletriptan vs. 50-53% sumatriptan for the first "efficacy" outcome described above, but only 16-17% vs. 14-16% for the second more rigorous "effectiveness" outcome [7]. For a health economic study, the really useful clinical outcome is what is required.…”
Section: Intangiblementioning
confidence: 99%
“…For example, one study looked at eletriptan vs. sumatriptan using the more complex outcome measure described above [7]. Another used another composite endpoint of sustained freedom from pain and no adverse effects to compare almotriptan and sumatriptan [12].…”
Section: Cost Effectiveness Analysismentioning
confidence: 99%